Knowledge, attitude and practices regarding HIV/ AIDS among dental students at Medunsa Oral Health centre - Galane, Mpatikana Leslie (University of Limpopo (Medunsa Campus), 2014)
Background: The HIV pandemic continues to be a major public health problem in Sub-Saharan Africa where 22.5 million people were infected with HIV in 2009 and South Africa remains one amongst the countries with the highest HIV epidemic. The number of HIV-positive and AIDS patients is increasing annually and there are no specialised oral health institutions that provide oral health care to HIV/AIDS patients. HIV and AIDS continues to have profound impact on all health training and education (Medical, Dentistry, Nursing etc.) and clinical care, hence it is crucial for all the health care students to be educated about HIV/AIDS disease. Dental student’s knowledge about HIV/AIDS, attitudes towards HIV-positive patients and infection control practices are of importance as they are the future oral health care providers. The Purpose: The purpose of the study was to determine the knowledge, attitudes and practices of third, fourth and fifth year dental students on HIV-positive and AIDS patients at the Medunsa Oral Health Centre (MOHC). Materials and Methods: This was a cross-sectional study conducted among 139 dental students at MOHC using a self administered questionaire with 30 closedended questions. T-test, one-way Anova (analysis of variance), multiple regressions and Pearson’s correlation were applied by Stata IC/10 to assess, determine and describe the knowledge, attitude and infection control practices of third, fourth and fifth year dental students, respectively and also find an association between demographic variables, knowledge, attitudes and practices. Results: The response rate was 86% (120/139), 33 of third year, 47 of fourth year and 40 of fifth year dental students. Gender was statistically significant towards knowledge and females were more knowledgeable about HIV/AIDS as compared to males (p=0.058). However, almost (98.3%) all dental students were not sure “HIV increases other infections, including oral infections as well”. More than half (53.1%) of third year dental students were not sure “persistent generalised lymphadenopathy vi is associated with stage 2 of HIV infection”. In this study, ethnic groups and level of study (BDS4 & BDS5) were found to be significant predictors of attitude regarding HIV-positive patients (p=0.001) (p=0.055) (p=0.001). Practice was found to be a significant predictor of knowledge regarding HIV/AIDS (p=0.046). Pearson’s correlation coefficient showed students with positive attitude scores had significantly excellent practice regarding HIV/AIDS (r=0.2912) (p=0.001). Good knowledge translates into excellent infection control practices, whilst positive attitude towards HIV/AIDS patients yield excellent infection control practices. Conclusion: The dental students at MOHC relatively have a good understanding of HIV/AIDS (particularly the mode of transmission) but to lesser extent, disease progress and oral manifestation. The lack of knowledge on HIV/AIDS and inconsistency regarding certain infection control procedures may be a reflection of insufficient HIV/AIDS teaching and clinical supervision of students in the wards. There is a need to improve the current dental curriculum by including HIV/AIDS module and incorporate a clinical component of dental screening at the ARV clinics.
Thesis (MPH) -- University of Limpopo, 2012.
Keywords: HIV; HIV infection